PEDAGOGICAL RESEARCH METHODS AND THEIR PRACTICAL SIGNIFICANCE IN THE EDUCATIONAL PROCESS - Ashurova Madina Isroil qizi (Bright Mind Publishing, 2025)
This article examines the main scientific research methods used in modern pedagogical inquiry, including observation, interview, questionnaire, document analysis, tests, pedagogical analysis, children's creative work analysis, pedagogical experiment, and mathematical-statistical methods. The theoretical foundations and practical significance of these methods are analyzed based on pages 15–20 of the textbook Umumiy Pedagogika. The study argues that these methods play a crucial role in improving the quality of education, understanding learners’ development, and organizing pedagogical processes on a scientific basis.
Keywords: Pedagogical research, observation method, questionnaire, interview, experiment, statistical analysis, educational diagnostics.